Multicenter, open-label, extension trial to evaluate the long-term efficacy and safety of early versus delayed treatment with tolvaptan in autosomal dominant polycystic kidney disease: the TEMPO 4:4 Trial. (31st March 2017) - Torres, Vicente E; Chapman, Arlene B; Devuyst, Olivier; Gansevoort, Ron T; Perrone, Ronald D; Dandurand, Ann; Ouyang, John; Czerwiec, Frank S; Blais, Jaime D; ,
Abstract: Background: In TEMPO 3:4, the vasopressin V2 receptor antagonist tolvaptan slowed total kidney volume (TKV) growth and estimated glomerular filtration rate (eGFR) decline relative to placebo. Methods: TEMPO 4:4 was designed to provide an additional 2 years of data on the long-term safety and efficacy of tolvaptan in subjects completing TEMPO 3:4. The objective was to assess the disease-modifying effects of tolvaptan on TKV and eGFR end-points including change from baseline over the combined duration of TEMPO 3:4 and TEMPO 4:4, and non-inferiority of slopes during TEMPO 4:4. Results: Of the 1445 subjects randomized to TEMPO 3:4, 871 (60.3%) enrolled in TEMPO 4:4. Percent changes in TKV from TEMPO 3:4 baseline to TEMPO 4:4 Month 24 were 29.9% and 31.6% (prior tolvaptan versus prior placebo, P = 0.38). Adjusting for baseline covariates improved the TKV treatment difference at Month 24 in TEMPO 4:4 from −1.70% to − 4.15% between the groups (P = 0.04). Slopes of TKV growth during TEMPO 4:4 were higher in early- versus delayed-treatment groups (6.16% versus 4.96% per year, P = 0.05). Analysis of secondary eGFR endpoints demonstrated a persistent effect on eGFR (3.15 mL/min/1.73 m 2, P < 0.001), and non-inferiority in eGFR slopes. The safety profile on exposure to tolvaptan in TEMPO 4:4 was similar to that in TEMPO 3:4. Conclusions: The results of TEMPO 4:4 support a sustained disease-modifying effect of tolvaptan on eGFR. The lack of a sustained treatment difference on TKV may be accounted for by limitations of the trial design, including loss of randomization and baseline imbalances ensuing TEMPO 3:4. The safety profile was similar to that observed in TEMPO 3:4.